Integration of MEMS inertial sensors towards commercially-viable tracking devices - Kor, Ronnie Xian Thong (2013)
It is hoped that this device will be implemented in hospices and nursing homes, as well as studio apartments. This will not only help to reduce the incidnce of falls among elderlies, but also encourage them to become more independent in self-care. [1st Award]